The Review África: Textual and Visual Performance of Africanism During Franco’s Dictatorship (1942-1950) - López Sánchez, José María; Puig-Samper Mulero, Miguel Ángel (Hispania Nova, 2023)
The review África was born in 1924 as a space for cultural sociability for the Africanist army. After the Civil War, the magazine was republished by military officers who, from the Presidency of the Government, tried to promote an Africanism that related to the army’s actions in Morocco before the war, but which during the post-war period required the construction of the legitimacy of the new regime and its colonial action in Africa. The magazine was a key factor in the textual and visual construction of this Africanism. In its pages a discourse was gestated that fed some of the basic characteristics of what we understand Francoism to be, and África was fundamental to this.
Keywords: africanism; francoism; colonialism; Morocco; Sahara; Guinea